Enhancing Junior High School Science Literacy through TPACK-Integrated Virtual Laboratory Modules - Iwan Wicaksono; Indrawati Indrawati; Sallimah Binti Hj Mohd Salleh; Sri Astutik; Pramudya Dwi Aristya Putra (FKIP Universitas Lampung, 2026)
The persistently low level of science literacy among Indonesian students, as evidenced by stagnant PISA 2022 results remaining below the OECD average, underscores a critical need to transform teaching materials to be more adaptive to technological advances. This research addresses the lack of pedagogically integrated materials on technological aspects, which often hinders students' ability to interpret scientific phenomena. To bridge this gap, the study aimed to develop science learning modules based on the Technological Pedagogical Content Knowledge (TPACK) framework and to test their validity, practicality, and effectiveness in improving junior high school students' science literacy. Following the 4D developmental model, Define, Design, Develop, and Disseminate, the research involved 120 seventh-grade students from the former Besuki Residency and 25 teachers from the East Java Science Teacher Working Group. Data collection employed expert validation sheets, user-response questionnaires, and science literacy tests, which were analyzed using the Normalized Gain (N-gain) formula. The results indicated that the TPACK-based module demonstrated high validity, with a score of 88.97% from media and materials experts. In terms of practicality, the module earned an average of 90.9%, supported by a 91.55% positive student response rate. The effectiveness test demonstrated a significant increase in science literacy, with an average N-gain of 0.70 (high category), with the problem-solving indicator showing the most substantial growth. During the dissemination stage, the module was distributed digitally to the East Java Science Teacher Working Group, where validation by 25 practicing teachers yielded a 92.4% feasibility score. This study concludes that TPACK-based modules are highly effective modern instruments for enhancing scientific competence. By integrating interactive simulations and virtual laboratories, these modules overcome physical facility limitations, making them highly suitable for widespread adoption within the national science curriculum to foster a more technologically literate generation. Keywords: science literacy, students, teaching module, TPACK, the development.